2016
DOI: 10.1007/s10854-016-4985-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of titania thin films grown by dip-coating technique

Abstract: A dip-coating technique was employed to prepare anatase phase of titania thin films. Fluorine doped tin oxide substrates were used to prepare titania thin films. The samples were annealed at 550°C for 18 h. X-ray diffraction results revealed the amorphous and anatase phases of TiO 2 for as-synthesized and annealed samples, respectively. The crystallite size of anatase TiO 2 thin films was almost 25 nm for annealed samples. UV-visible confirmed the energy band gap 3.86 and 3.64 eV for as-prepared and calcinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(41 citation statements)
references
References 39 publications
(25 reference statements)
3
38
0
Order By: Relevance
“…Table I depicts the variation of the crystallite size, D (coherently diffracting domains) calculated from the Ni 3 N(111) peak as a function of energy implantation [21]. It is well known that the size of the particles depends on implantation energy [25] and the crystallinity is improved upon heat treatments [27,30]. From data of Table I, it is observed that the crystallite size increases with the implantation energy.…”
Section: Xrd Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Table I depicts the variation of the crystallite size, D (coherently diffracting domains) calculated from the Ni 3 N(111) peak as a function of energy implantation [21]. It is well known that the size of the particles depends on implantation energy [25] and the crystallinity is improved upon heat treatments [27,30]. From data of Table I, it is observed that the crystallite size increases with the implantation energy.…”
Section: Xrd Resultsmentioning
confidence: 98%
“…The Scherrer formula is used to obtain the crystallite size, D (coherently diffracting domains) [23][24][25][26][27]:…”
Section: Xrd Resultsmentioning
confidence: 99%
“…Figure shows the FTIR spectra of β‐CD, β‐CD‐MAH, non‐imprinted polymer and Cu(II)‐imprinted polymer. The FTIR spectra show a peak due to an asymmetrical stretching vibration between 3400 and 3500 cm −1 , which can be attributed to the O–H stretching vibration in β‐CD . After the reaction of β‐CD with MAH, a characteristic peak due to the symmetric stretching vibration of unsaturated carboxylic acid ester appeared at 1728 cm −1 , while the ring vibration peak was still present at 580 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra show a peak due to an asymmetrical stretching vibration between 3400 and 3500 cm −1 , which can be attributed to the O-H stretching vibration in -CD. 29,30 After the reaction of -CD with MAH, a characteristic peak due to the symmetric stretching vibration of unsaturated carboxylic acid ester appeared at 1728 cm −1 , while the ring vibration peak was still present at 580 cm −1 . The peak at 940 cm −1 due to vibration of the backbone containing the -1,4 glycosidic bond was in agreement with the structure of -CD.…”
Section: Resultsmentioning
confidence: 99%
“…Modification of materials surface helps to enhance their functional characteristics and spread technical applications [1][2][3][4][5][6]. Nowadays, there are a lot of processing methods for modification of surface and near-surface areas [7][8][9][10][11][12]. These methods provide etching, anodization, structuration, oxidation, nitridization, etc.…”
mentioning
confidence: 99%